Mindfulness-Based Stress Reduction Benefits Psychological Well-Being, Sleep Quality, and Athletic Performance in Female Collegiate Rowers - Jones, Bethany J.; Kaur, Sukhmanjit; Miller, Michele; Spencer, Rebecca M. C. (Frontiers in Psychology, 2020)
Factors such as psychological well-being, sleep quality, and athletic coping skills can influence athletic performance. Mindfulness-based interventions, including mindfulness-based stress reduction (MBSR), have been shown to benefit these factors, suggesting they may, at least indirectly, benefit athletic performance. Moreover, while mindfulness training has been linked to better accuracy in some high-precision sports, whether it can improve non-precision elements of athletic performance is unclear. The objective of this study was to investigate the influence of MBSR on psychological well-being, sleep, athletic coping skills, and rowing performance in collegiate rowers in a controlled experimental design. Members of a Division I NCAA Women’s Rowing team completed either an 8-week MBSR course along with their regular athletic training program (Intervention group) or the athletic training program alone (Control group). Measurements of interest were taken at baseline and again either during or shortly following the intervention. In contrast to the Control group, the Intervention group showed improvements in psychological well-being, subjective and objective sleep quality, athletic coping skills, and rowing performance as measured by a 6,000-meter ergometer test. Improvements in athletic coping skills, psychological well-being, and subjective sleep quality were all correlated with increases in mindfulness in the Intervention group. These results suggest that mindfulness training may benefit non-precision aspects of athletic performance. Incorporating mindfulness training into athletic training programs may benefit quality of life and performance in student athletes.